Detecting dengue fever based on nature language processing - Xia, Linpeng (Nanyang Technological University, 2023)
Dengue Fever is becoming an increasingly severe problem all over the world. Besides curing dengue, detecting and preventing Dengue Fever is a very important way to protect public health. With the prevailing of social media, lots of information can be extracted utilizing Nature Language Processing. This thesis collects publicly available data from Twitter to build a standard dataset about Dengue Fever and utilizes several kinds of neural networks to do Dengue detection. The experiment results show that CNN network is the best for this kind of job.